The growth-employment-poverty nexus in Latin America in the 2000s: Venezuela country study - Guillermo Cruces; Gary Fields; David Jaume; Mariana Viollaz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Venezuela experienced slow economic growth during the 2000s. The economy suffered a recession in the early years of the period and during the international crisis of 2008, but most labour market indicators improved and moved along with the business cycle over the period. The only indicators that did not improve were the composition of employment by occupational position and the percentage of workers registered with social security, which remained essentially unchanged. Most of the labour market indicators were affected negatively by the international crisis, and some of them had not recovered their pre-crisis levels by 2012.
Keywords: O15; J01; J30; 330; Venezuela; Latin America; inclusive growth; labour market; poverty